2014
DOI: 10.1134/s0030400x14060137
|View full text |Cite
|
Sign up to set email alerts
|

Crystal field and magnetoelastic interactions in Tb2Ti2O7

Abstract: Abstract-In terms of a semi-phenomenological exchange charge model, we have obtained estimates of parameters of the crystal field and parameters of the electron-deformation interaction in terbium titanate Tb 2 Ti 2 O 7 with a pyrochlore structure. The obtained set of parameters has been refined based on the analysis of spectra of neutron inelastic scattering and Raman light scattering, field dependences of the forced magnetostriction, and temperature dependences of elastic constants. INTRODUCTIONInterest in in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 24 publications
1
19
0
1
Order By: Relevance
“…4,7,[14][15][16][17][18][19][20] Unfortunately, there are significant discrepancies between the published sets of crystal field parameters. These are partly caused by the fact that some of the models employ a truncated basis containing only the 13 states of the ground state 7 F 6 manifold, whereas others include all the states in the f 8 configuration of Tb 3+ .…”
Section: -10mentioning
confidence: 99%
“…4,7,[14][15][16][17][18][19][20] Unfortunately, there are significant discrepancies between the published sets of crystal field parameters. These are partly caused by the fact that some of the models employ a truncated basis containing only the 13 states of the ground state 7 F 6 manifold, whereas others include all the states in the f 8 configuration of Tb 3+ .…”
Section: -10mentioning
confidence: 99%
“…The local magnetic field affecting the Nd 3+ ions, H loc = H + H exch + H dip − H D , involves the external field H, the exchange and dipolar fields H exch and H dip , respectively, corresponding to anisotropic exchange and magnetic dipolar interactions between the Nd 3+ ions that are considered within the self-consistent field approximation, and the demagnetizing field H D = 4πN M/3, where N is the demagnetizing factor, M = n m n /ν is the magnetization, and ν = a 3 /4 is the unit cell volume. There [52,53] with the parameters of the crystal lattice determined in the present work, are given in column A. The final values of the CF parameters used to simulate the dc susceptibility and the magnetization data are given in column B (see text for details).…”
Section: Crystal Field Parametersmentioning
confidence: 99%
“…[51]. The initial values of the CF parameters were calculated in the framework of the exchange charge model [52,53] by making use of the parameters of the crystal lattice determined in the present work (see column A in Table IV). The effective ionic charges were taken from Ref.…”
Section: Crystal Field Parametersmentioning
confidence: 99%
“…However, experimental studies revealed a lack of static order or spin freezing in Tb 2 Ti 2 O 7 down to 70 mK [3,4], and more recently 57 mK [5]. Subsequently, enormous efforts have been undertaken to uncover the origin of the spin liquid state in Tb 2 Ti 2 O 7 .A further complication in Tb 2 Ti 2 O 7 is the coupling of magnetic and lattice degrees of freedom [6][7][8][9]. It has been suggested that hybridized magnetoelastic excitations may be responsible for the suppression of magnetic order in Tb 2 Ti 2 O 7 [10].…”
mentioning
confidence: 99%
“…A further complication in Tb 2 Ti 2 O 7 is the coupling of magnetic and lattice degrees of freedom [6][7][8][9]. It has been suggested that hybridized magnetoelastic excitations may be responsible for the suppression of magnetic order in Tb 2 Ti 2 O 7 [10].…”
mentioning
confidence: 99%